2014
DOI: 10.1177/0284185113494984
|View full text |Cite
|
Sign up to set email alerts
|

US-guided transthoracic biopsy of peripheral lung lesions: pleural contact length influences diagnostic yield

Abstract: In US-guided transthoracic biopsy of peripheral lung lesions, the LPCAL of the lesions is an important factor for a correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
(40 reference statements)
5
34
0
Order By: Relevance
“…In addition, a good acoustic window may not be available with US if the contact area between the lesion and the pleura is small, but it may be feasible to guide the needle to such lesions under CT guidance. [24]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a good acoustic window may not be available with US if the contact area between the lesion and the pleura is small, but it may be feasible to guide the needle to such lesions under CT guidance. [24]…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ultrasound-guided transthoracic biopsy of mediastinal lesions has attracted clinical attention due to its advantages of being economic, convenient, safe, quick, and no radiation (1-3). However, conventional ultrasound (US) cannot clearly reveal the internal structures of the mediastinal lesions and the detection of superficial vessels or presence of internal necrotic tissue was limited (4). As a consequence, there is a risk of complications, such as bleeding, or false-negative results of biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Jeon et al reported that the diagnostic accuracy of US-guided biopsy using B-mode was significantly increased for lesions in which the pleural-lesion contact area was ≥30 mm on the CT images [8]; moreover, for lesions with LPCAL values ≤ 30 mm, the diagnostic accuracy decreased from 98% to 85.4%. They concluded that US-guided biopsy of pulmonary lesions might be performed more easily when the lesion has a contact area as wide as the US window, which permits a flexible approach route.…”
Section: Discussionmentioning
confidence: 99%